Opposing Roles of Leptin and Ghrelin in the Equine Corpus Luteum Regulation: An In Vitro Study. (13th July 2014) - Galvão, António; Tramontano, Angela; Rebordão, Maria Rosa; Amaral, Ana; Bravo, Pedro Pinto; Szóstek, Anna; Skarzynski, Dariusz; Mollo, Antonio; Ferreira-Dias, Graça
Abstract : Metabolic hormones have been associated with reproductive function modulation. Thus, the aim of this study was: (i) to characterize the immunolocalization, mRNA and protein levels of leptin (LEP), Ghrelin (GHR) and respective receptors LEPR and Ghr-R1A, throughout luteal phase; and (ii) to evaluate the role of LEP and GHR on progesterone (P4 ), prostaglandin (PG) E2 and PGF2 α, nitric oxide (nitrite), tumor necrosis factor- α (TNF); macrophage migration inhibitory factor (MIF) secretion, and on angiogenic activity (BAEC proliferation), in equine corpus luteum (CL) from early and mid-luteal stages. LEPR expression was decreased in late CL, while GHR/Ghr-R1A system was increased in the same stage. Regarding secretory activity, GHR decreased P4 in early CL, but increased PGF2 α, nitrite and TNF in mid CL. Conversely, LEP increased P4, PGE2, angiogenic activity, MIF, TNF and nitrite during early CL, in a dose-dependent manner. The in vitro effect of LEP on secretory activity was reverted by GHR, when both factors acted together. The present results evidence the presence of LEP and GHR systems in the equine CL. Moreover, we suggest that LEP and GHR play opposing roles in equine CL regulation, with LEP supporting luteal establishment and GHR promoting luteal regression. Finally, a dose-dependent luteotrophic effect of LEP was demonstrated.